II-03 Pathogenesis of diffuse alveolar haemorrhage (DAH) in lupus. (31st August 2016) - Zhuang, Haoyang; Han, Shuhong; Lu, Li; Qi, Xin; Shumyak, Stepan; Yang, Lijun; Reeves, Westley
Abstract : Background: Diffuse alveolar haemorrhage (DAH) in lupus patients carries a mortality rate of over 50%. C57BL/6 mice with pristane-induced lupus develop DAH closely resembling the human disease. The role of cell death, complement, immunoglobulin, Toll-like receptors, and myeloid cells was examined in pristane-treated mice with DAH. Materials and methods: Clinical/pathological and immunological manifestations of pristane-induced lupus in gene-targeted vs. wild type mice were compared with the manifestations in SLE patients. Tissue distribution of pristane was examined histologically and by mass spectrometry. The cell types responsible for disease were examined by in vivo depletion using clodronate liposomes (CloLip) and anti-neutrophil monoclonal antibodies (GR1). The effect of treatment with the C3b-analogue cobra venom factor (CVF) was examined. Results: After peritoneal injection, pristane was detected in the lung by mass spectrometry and oil red staining, and was found to induce cell death, phagocytosis of the dead cells and erythrocytes by alveolar macrophages, consolidation of the alveolar spaces by erythrocytes and inflammatory cells, thickening of the alveolar wall, and extensive cellular proliferation (Ki-67 staining) within the alveolar septa. Small vessel vasculitis characterised by perivascular neutrophils and F4/80 + macrophages was present. Lung tissue from SLE patients with DAH had a similar appearance. B-cell-deficient (μMT) mice were resistant to the induction of DAH, but susceptibility was restored by infusing IgM. C3-deficient and CD18-deficient mice also were resistant, and DAH could be prevented in wild-type mice by depleting complement with CVF. Induction of DAH was independent of MyD88, TRIF, TNFα, and type I interferon, but mortality was increased in IL-10-deficient mice. In vivo neutrophil depletion had no effect on susceptibility, whereas treatment with CloLip depleted both resident alveolar macrophages and presumptive bone marrow-derived F4/80 + macrophages while preventing DAH, suggesting that macrophages are central to DAH pathogenesis. Conclusion: Induction of DAH in pristane-lupus is likely to involve opsonization of dead cells in the lung by natural IgM and complement followed by complement receptor 3 (CD11b/CD18) and/or CR4 (CD11c/CD18)-mediated phagocytosis, resulting in lung inflammation. Disease is macrophage-dependent and independent of type I interferon, TNFα, MyD88, and neutrophils. Complement inhibition and/or macrophage-targeted therapies may be attractive candidates for treating SLE-associated DAH.